Working girl - Nichols, Mike; Wade, Kevin; Griffith, Melanie 1957-; Weaver, Sigourney 1949-; Ford, Harrison 1942-; Simon, Carly (Twentieth Century Fox Home Entertainment, 2002)
Beauty.Brains.Charm. Tess Mcgill has them all. In fact she's got everything going for her except the right haircut, the right clothes and most importantly, the right job. Ambushed one too many times in her struggleto get out of the Wall Street secretarial pool and onto management trcak. Tess decides to take matters into her own hands. When her classy, seductive and treacherous boss breaks a leg skiing, Tess steps, literally into her boss's shoes-as well as her apartment, her corner office and her